Wedle dobrych obyczajów czy zgodnie z zasadami współżycia społecznego? Uwagi na tle funkcjonowania klauzuli generalnej z Ustawy o zwalczaniu nieuczciwej konkurencji - Laszczyk, Anna, Michał Gajdus (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2012)
The aim of this paper is to analyse the application of the good practices blanket clause on the example of the Suppression of Unfair Competition Act. First, the authors characterise the general functions and use of blanket clauses, then they focus on the one of their main interest. The authors analyse the origin of the clause as well as the actual understanding of good practice both in the doctrine and in judicial decisions, and subsequently compare the functioning, or application, of good practices and principles of community life to conclude that the application of a good practice clause is not efficient and its use in the future should be discontinued.
According to good practices clause or the principles of community life? Commentson the application of a blanket clause on the example of the Suppression of UnfairCompetition Act
Keywords: unfair competition; blanket clauses; good practices; principles of community life